Towards Measuring the Level of Identification with Multicultural Practices and Values in German National Culture: A Critical Discourse Analytic Study on Multicultural Representations in the German National Integration Plan - Rösch, Sven (My University, 2010)
This study assesses the extend to which multicultural values and practices are held to be important in German cultural identity. The basic theoretical assumption is that cultural identity is shaped discursively in the mode of narration – text in particular. Therefore, a discourse analytic study is conducted that searches for references relating to ideal forms of multicultural values and practices in order to evaluate the current form of German multicultural identity. The study is based on the German National Integration Plan (Die Bundesregierung 2007) – a core document of German efforts towards building a multicultural society and introducing an active integration policy. The findings will be compared to reflections on German multiculturalism in Ha (2009) and Zaimoglu (2007 [1995]. The material is analyzed under an analytic grid combining Fairglough's (2002) framework for critical discourse analysis and a set of analytical categories (ideal multicultural values and practices). Based on the material under analysis, the study shows that German cultural identity draws little on ideal forms of multicultural practices and values. Rather, the NIP (Die Bundesregierung 2007) attempts to introduce a multicultural discourse in the debate around integration policy and has to be understood as a communicative effort in negotiating and shaping a paradigm shift towards the incorporation of multicultural values in German cultural identity – a development that, based on the analysis of social practices, has not yet taken place. Critical discourse analysis suggests that a number of multicultural practices and values are in fact held important in German cultural identity but yet remain on a rather superficial level of language.
Keywords: Fairclough; Der Nationale Integrationsplan; multiculturalism; cultural identity; discourse analysis; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|